Missed Acute Myocardial Infarction (MAMI) in a rural and regional setting. (March 2019) - Williams, Trent; Savage, Lindsay; Whitehead, Nicholas; Orvad, Helen; Cummins, Claire; Faddy, Steven; Fletcher, Peter; Boyle, Andrew J.; Inder, Kerry Jill
Abstract: Background: Delay in treatment and/or failure to provide reperfusion in ST-segment elevation myocardial infarction (STEMI) impacts on morbidity and mortality. This occurs more often outside metropolitan areas yet the reasons for this are unclear. This study aimed to describe factors associated with missed diagnosis of acute myocardial infarction (MAMI) in a rural and regional setting. Methods: Using a retrospective cohort design, patients who presented with STEMI and failed to receive reperfusion therapy within four hours were identified as MAMI. Univariate analyses were undertaken to identify differences in clinical characteristics between the treated STEMI group and the MAMI group. Mortality, 30-day readmission rates and length of hospital stay are reported. Results: Of 100 patients identified as MAMI (70 male, 30 female), 24 died in hospital. Demographics and time from symptom onset were similar in the treated STEMI and MAMI groups. Of the MAMI patients who died, rural hospitals recorded the highest inpatient mortality (69.6% p  = 0.008). MAMI patients compared to treated STEMI patients had higher 30 day readmission (31.6% vs 3.3%, p  = 0.001) and longer length of stay (5.5 vs 4.3 days p  = 0.029). Inaccurate identification of STEMI on electrocardiogram (72%) and diagnostic uncertainty (65%) were associated with MAMI. The Glasgow algorithm to identify STEMI was utilised on 57% of occasions, with 93% accuracy. Conclusion: Mortality following MAMI is high particularly in smaller rural hospitals. MAMI results in increased length of stay and readmission rate. Electrocardiogram interpretation and diagnostic accuracy require improvement to determine if this improves patient outcomes.